Pengaruh Profitabilitas, Likuiditas dan Leverage terhadap Return Saham dengan Kebijakan Properti sebagai Variabel Moderasi pada Perusahaan Sektor Industri Property, Real Estate and Building Construction di Bursa Efek Indonesia - Stefanny Novi Andarista; Michelle Angelina Setyawan; Yulius Jogi Christiawan (Business Accounting Review, 2020)
This research is aimed to study the effect of profitability, liquidity and leverage toward stock return with property regulation as moderating variable in property, real estate and building construction companies that were listed in Bursa Efek Indonesia. This research study was done using a quantitative method with 23 companies that was determined using purposive sampling with criteria of being listed before 2018 and were actively traded in the stock market during 2018, and has residential development for low-income community. 2nd and 4th quarterly reports were used for the research, thus creating 46 observation samples. The research was done by analyzing financial statements and analyzing using GRETL.The result of the analysis shows that profitability has a positive effect toward stock return, liquidity does not have a significant effect toward stock return, leverage has a negative effect toward stock return, and property regulation does not have a significant effect toward stock return. Moreover, property regulation is able to strengthen the effect of profitability toward stock return, weaken the effect of leverage toward stock return, and does not moderate the effect of liquidity toward stock return.